1980
DOI: 10.1111/j.1600-051x.1980.tb01963.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effects of initial, nonsurgical periodontal treatment (hygienic phase)

Abstract: Longitudinal studies have reported the effect of various modalities of periodontal surgery on pocket depth and attachment levels related to pretreatment measurements. However, possible changes in these measurements as a result of scaling, oral hygiene improvements and occlusal adjustment during the hygienic phase were not considered. The purpose of the present study was to examine the short-term effect of treatment of the hygienic phase in 90 patients with some pockets extending 4 mm or more apically to the CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
120
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(152 citation statements)
references
References 12 publications
28
120
1
3
Order By: Relevance
“…The mean gain in attachment level in both groups between baseline and 42nd day was highly significant (p value <0.01). These results were consistent with previous studies Attachment gain subsequent to subgingival scaling and improvement in oral hygiene appears to be due to the migration of dentogingival junction to or close to the apical level of root instrumentation during healing due to the reduction in the tissue inflammation following the removal of plaque and calculus, [2] and oral hygiene instructions that were given to the subjects. These results were found to be consistent with previous studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The mean gain in attachment level in both groups between baseline and 42nd day was highly significant (p value <0.01). These results were consistent with previous studies Attachment gain subsequent to subgingival scaling and improvement in oral hygiene appears to be due to the migration of dentogingival junction to or close to the apical level of root instrumentation during healing due to the reduction in the tissue inflammation following the removal of plaque and calculus, [2] and oral hygiene instructions that were given to the subjects. These results were found to be consistent with previous studies.…”
Section: Discussionsupporting
confidence: 81%
“…The clinical effect of scaling and rootplanning (SRP) are well documented. [2,4] These studies indicated that SRP decreased pocket probing depth and attachment level measurements particularly at the deeper sites. Microbiological studies on effect of SRP indicated that proportion of spirochetes and motile rods decline after SRP while cocci and non-motile rods increased Haffajee et al [5] reported that SRP alone has limited effect on some pathogenic species.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Thus we can begin to see a strong clinical argument for more regular periodontal maintenance therapy.…”
Section: What Is the Evidence For The Importance Of Maintenance?mentioning
confidence: 99%
“…This can be accomplished by thorough daily oral hygiene measures achieved by the patient (18), and by professionally performed mechanical debridement (3,6,19). Many patients avoid professional oral hygiene because of pain during treatment and fear of anaesthetic injection (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of scaling and root planing (SRP) combined with personal plaque control in the treatment of chronic periodontitis have been validated (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%